Relationship between Sleep Quality and Gait Speed in Geriatric Patients - Kaya, Tezcan; Nalbant, Ahmet; Yıldırım, İlhan; İşsever, Kubilay; Karacaer, Cengiz; Bilgin, Cahit; Vatan, Mehmet Bülent; Acar, Türkan (Journal of Liaquat University of Medical & Health Sciences, 2023)
OBJECTIVE: To identify the relationship between sleep quality and gait speed in geriatric patients. METHODOLOGY: This cross-sectional study involved 140 Geriatric patients (aged ?65 years) who consecutively applied for the internal medicine outpatient clinic of an Education Research Hospital between July and September 2021 using a non-probability consecutive sampling technique. Participants with cancer, rheumatic or muscle disease, insomnia, amputations or motor dysfunction in the extremities, Parkinson's or Alzheimer's disease, who could not walk alone, and those with cognitive impairment who could not answer questions were excluded. The Pittsburgh Sleep Quality Index (PSQI) assessed participants' sleep quality. Gait speed for a 4-meter distance was measured. Parameters were compared concerning sleep quality and gait speed. RESULTS: The gait speed of poor sleepers was significantly slower than good sleepers (p=0.012). Slow walkers were more prevalent among the poor than good sleepers (p=0.030). The median PSQI score of slow walkers was higher than that of normal walkers (p=0.009). The ratio of patients with poor sleep quality was significantly higher among slow walkers than among normal walkers (p=0.030). A significant positive correlation was found between the total PSQI score and gait speed time (r=0.250, p=0.003). The receiver operating characteristics curve of gait speed time was statistically significant for predicting poor sleep quality (AUC=0.629; p=0.012). CONCLUSION: Gait speed was slower in geriatric patients with poor sleep quality. Poor sleep quality and gait speed time were positively correlated, and gait speed was a predictor of sleep quality in geriatric patients.